VMP1-related autophagy induced by a fructose-rich diet in B-cells: its prevention by incretins - Maiztegui, Barbara (2017)
The aim of the present study was to demonstrate the role of autophagy and incretins inthe fructose-induced alteration of β-cell mass and function. Normal Wistar rats were fed(3 weeks) with a commercial diet without (C) or with 10% fructose in drinking water (F) aloneor plus sitagliptin (CS and FS) or exendin-4 (CE and FE). Serum levels of metabolic/endocrineparameters, B-cell mass, morphology/ultrastructure and apoptosis, vacuole membrane protein1 (VMP1) expression and glucose-stimulated insulin secretion (GSIS) were studied.Complementary to this, islets isolated from normal rats were cultured (3 days) without (C) orwith F and F + exendin-4 or chloroquine. Expression of autophagy-related proteins [VMP1and microtubule-associated protein light chain 3 (LC3)], apoptotic/antiapoptotic markers(caspase-3 and Bcl-2), GSIS and insulin mRNA levels were measured. F rats developed impairedglucose tolerance (IGT) and a significant increase in plasma triacylglycerols, thiobarbituricacid-reactive substances, insulin levels, homoeostasis model assessment (HOMA)for insulin resistance (HOMA-IR) and B-cell function (HOMA-B) indices. A significant reductionin B-cell mass was associated with an increased apoptotic rate and morphological/ultrastructuralchanges indicative of autophagic activity. All these changes were preventedby either sitagliptin or exendin-4. In cultured islets, F significantly enhanced insulinmRNA and GSIS, decreased Bcl-2 mRNA levels and increased caspase-3 expression.Chloroquine reduced these changes, suggesting the participation of autophagy in this process.Indeed, F induced the increase of both VMP1 expression and LC3-II, suggesting thatVMP1-related autophagy is activated in injured B-cells. Exendin-4 prevented islet-cell damageand autophagy development. VMP1-related autophagy is a reactive process againstF-induced islet dysfunction, being prevented by exendin-4 treatment. This knowledge couldhelp to use autophagy as a potential target for preventing progression from IGT to type 2diabetes mellitus.